Contemporary problems of Indian polity - Hans Raj (Delhi, 1983)
India constitution which was inaugurated on 26th Jan. 1950 has established Parliamentary democracy in the country. The system as established by law in India has come under heavy strains with the passage of time.
Keywords: Political Science